Analisis kemampuan pemahaman matematis siswa kelas VIII SMPN 3 ngamprah pada materi relasi dan fungsi - Fien Zenith; Jozua Sabandar; Risma Amelia (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The aim of this study was to describe how well students understood relational and functional mathematics. By examining the typical student responses to prepared instrument questions, descriptive qualitative research methodology is applied. The study's instrument was a written test of math comprehension that had six questions and three indicators of math understanding: classifying objects with specific properties in accordance with the concept, presenting the concept in various mathematical representations, and using a problem-solving strategy or algorithm. 30 pupils from SMPN 3 Ngamprah in grade VIII served as the study's subjects. According to the analysis's findings, class VIII pupils at SMPN 3 Ngamprah's mathematics knowledge abilities were rated as low, and students received a sufficient.